IDENTIFIKASI ISOLAT KULIT BATANG WARU (Hibiscus tiliaceus L.) MENGGUNAKAN SPEKTROSKOPI INFRAMERAH - Taupik, M.Sc, Muhammad; Adam Mustapa, Muhammad (State University of Gorontalo, 2019)
Waru (Hibiscustiliaceus L.) bark is a plant that is believed and used by community as a traditional medicine in treatment, especiallytotreat fever. This study aims to analyze the level of a secondary metabolite compound in the bark of waru (Hibiscustiliaceus L.) plant calculated using UV-Vis spectrophotometry and infrared methods. The method used to identify the flavonoid content is Thin Layer Chromatography (TLC) using eluent n-hexane and ethyl acetate at the best comparison (7:3). The result obtained from this study is waru bark extract containing flavonoid compound which is shown from the Rf value of the waru bark methanol extract of 0.82, which the value is close to the Rf value of quarcetine 0.83. Analysis of the flavonoid content of waru bark methanol extract has carried out on The Spectrophotometric UV-Vis at a wavelength of 382 nm and the total flavonoid content obtained is of 10 mg of waru bark methanol extract containing135.2166µg/mL flavonoid compound with percentage of 13.521% and on the Spetroscopy Infrared, based on the obtained peak shows the existence of functional groups of OH, CH aliphatic, C=C aromatic and C-O indicates that this isolat is a flavonoid compound.